A Methodology for the Design of Multichannel Service Processes - Sousa, Rui (2013)
This paper develops a methodology for the choice of the service channels that support the delivery to customers of the distinct stages of a service process. We build on the principles of Quality Function Deployment (QFD) to develop a stepwise procedure for: i) translating customer requirements into a service concept across distinct service stages; and ii) specifying the channels for customer interaction at each stage. An illustration of the application of the methodology for designing an urban gourmet grocery service is provided.